Early Holocene Antarctic climate variability - Drivers and consequences as captured by major ions in the Roosevelt Island Climate Evolution (RICE) ice core - Lukas Johannes Eling (2019)
In a warming world, rapid disintegration of the West Antarctic Ice Sheet (WAIS) remains a primary uncertainty in the Intergovernmental Panel on Climate Change (IPCC) sea level rise projections. A deep ice core was drilled at the northeastern edge of the Ross Ice Shelf as part of the Roosevelt Island Climate Evolution (RICE) project. The site is located in a major drainage pathway of the marine based WAIS and the primary focus of the RICE project is to provide new insights into our understanding of the stability of the Ross Ice Shelf (RIS) in a warming climate and associated sea-level rise contributions of the WAIS. Due to its coastal location Roosevelt Island is sensitive to ice-ocean-atmosphere interactions and is characterised by high snow accumulation of 20 cm per year affording a high resolution ice core record. This PhD project focuses on the Early Holocene major ion record, comprising measurements of the anions Cl– , NO – 3 , SO 2 – 4 and MSA– and the cations Na+, K+, Mg2+ and Ca2+ as they can provide insight into changing atmospheric circulation patterns, sea ice conditions and primary productivity. This time period is particularly interesting as recent results from marine studies, integrated with the latest generation of ice sheet models, suggest that the majority of deglacial retreat of Ross Sea grounded ice occurred during the Early Holocene. Using chemical signatures in a seasonally resolved section of the core the RICE sea salt (ss) aerosol (e.g. ssNa+) is shown to be sensitive to sea ice extent in the Ross Sea. The biogenic sulphur species methanesulphonic acid (MSA– ) is used to investigate sea ice extent and primary productivity in the Ross Sea region. Primary productivity responds to availability of light and nutrients and this makes MSA– a sensitive recorder of sea ice conditions and perhaps upwelling of nutrient rich deep waters. The common centennial scale variability in the RICE MSA– and sea salt proxy during the early Holocene optimum is interpreted as a reflection of the thermohaline ...